Plasma leptin level is associated with cardiac autonomic dysfunction in patients with type 2 diabetes: HSCAA study - Kurajoh, Masafumi (Cardiovasc Diabetol, 2015)
BACKGROUND: It has been shown that visceral fat accumulation is associated with autonomic dysfunction, though the precise mechanism remains unclear. A recent basic study found that leptin can directly modulate autonomic function through the dorsomedial hypothalamus in relation to obesity. Here, we investigated the mutual relationships among plasma leptin, visceral fat accumulation, and cardiac autonomic dysfunction in patients with type 2 diabetes. METHODS: This cross-sectional study included 100 diabetic patients, and 100 age- and gender-matched non-diabetic patients with cardiovascular risk factors. Plasma leptin and soluble leptin receptor levels, visceral fat area (VFA), and heart rate variability (HRV) were determined in addition to classical cardiovascular risk factors. RESULTS: In the type 2 diabetic patients, VFA was significantly (p < 0.05) and inversely associated with HRV parameters (SDNN: r = −0.243; SDANN5: r = −0.238), while the plasma level of leptin, but not soluble leptin receptor, was also significantly (p < 0.05) and inversely associated with HRV parameters (SDNN: r = −0.243; SDANN5: r = −0.231). Multiple regression analysis showed that plasma leptin was significantly associated with SDNN and SDANN5 independent of other factors, including age, gender, presence of hypertension and dyslipidemia, duration of diabetes, HbA1c, and eGFR. Furthermore, the relationship of leptin with SDNN and SDANN5 (β = −0.279 and −0.254, respectively) remained significant (p < 0.05) after adjustment for VFA. In patients without diabetes, no significant associations were observed between leptin and any of the HRV parameters. CONCLUSIONS: Hyperleptinemia may be involved in cardiac autonomic dysfunction in patients with type 2 diabetes and visceral obesity.